2019
DOI: 10.3390/rs11111389
|View full text |Cite
|
Sign up to set email alerts
|

A Sub-Regional Extraction Method of Common Mode Components from IGS and CMONOC Stations in China

Abstract: There is always a need to extract more accurate regional common mode component (CMC) series from coordinate time series of Global Positioning System (GPS) stations, which would be of great benefit to describe the deformation features of the Earth’s surface with more reliability. For this purpose, this paper combines all 11 International Global Navigation Satellite System (GNSS) Service (IGS) stations in China with over 70 stations selected from the Crustal Movement Observation Network of China (CMONOC) to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Moreover, we would like to emphasise the importance of the choice of the GNSS network for performing PCA [40]. The choice of a homogeneous network is wise in order to equally distribute the signal across the entire region.…”
Section: Common Mode Estimation In Gnssmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we would like to emphasise the importance of the choice of the GNSS network for performing PCA [40]. The choice of a homogeneous network is wise in order to equally distribute the signal across the entire region.…”
Section: Common Mode Estimation In Gnssmentioning
confidence: 99%
“…Finally, in order to search for the true geophysical signals in interannual variations, the extraction of spatial common modes from the signal is usually carried out [37]. This can be conducted using different techniques: principal component analysis (PCA) [38][39][40], independent component analysis (ICA) [41], or robust statistical methods [42]. Since the sources are not necessarily independent, it is reasonable to choose PCA in order to compare the interannual signal from GNSS with the signals derived from hydrological models, GRACE (Gravity Recovery and Climate Experiment), and the GRACE Follow-On time variable gravity field [43].…”
Section: Introductionmentioning
confidence: 99%
“…There are few studies on the extraction and removal of CME at large spatial scales [20][21][22], and these focused only on the effect of different filtering methods for large spatial scales. Related studies have shown that the spatial responses (SRs) of PCA/ICA to partial versus whole principal/independent components differ significantly across the study regions [23][24][25][26][27], with small spatial scales of the region filtering results being better than those of large spatial scales [28]. Delineating subregions exponentially increases the workload, but there is no uniform delineation standard.…”
Section: Introductionmentioning
confidence: 99%
“…A seismic jump is a co-seismic slip and its following motion is a post-seismic slip. To model a post-seismic decay motion, exponential function [Nikolaidis, 2004], logarithmic function [Bevis and Brown, 2014;Itoh and Nishimura, 2016;Wu et al, 2019] or a combination of them [Tobita, 2016;Klos et al, 2019] can be used.…”
Section: Introductionmentioning
confidence: 99%
“…Two usual methods to study the spatial correlation are the stacking method [Wdowinski et al, 1997;Nikolaidis, 2004;Marquez-Azua and De Mets, 2003;Wdowinski et al, 2004;Wang et al, 2012;Jiang et al, 2018] and the Empirical Orthogonal Function (EOF) method [Teferle et al, 2008]. In the branch of the EOF method, the Principal Component Analysis (PCA) method [Dong et al, 2006;He et al, 2015;Liu et al, 2015;Borghi et al, 2016;Gruszczynski et al, 2018;Birhanu et al, 2018;Wu et al, 2019;Tan et al, 2020] and the Karhunen-Loeve Expansion (KLE) method [Dong et al, 2006] can be mentioned. In the stacking method, the Common Mode Error (CME) parameter is calculated to remove the spatial correlation between the stations.…”
Section: Introductionmentioning
confidence: 99%